Antarctic population of Anteholosticha sigmoidea (Foissner, 1982) Berger, 2003 (Ciliophora: Urostylidae) with notes on its phylogenetic position - Kim, Kang-San; Ji, Su-Jung; Kim, Sanghee; Min, Gi-Sik (Zootaxa, 2021)
Anteholosticha sigmoidea (Foissner, 1982) Berger, 2003 was isolated from a wet soil sample collected on King George Island, Antarctica. Morphological observations and molecular phylogenetic analyses based on the gene sequences of small subunit ribosomal RNA (18S rRNA) were used to identify the species. Anteholosticha sigmoidea can be divided into two groups: group I (three populations described by Foissner 1982) and group II (described by Foissner 1984) based on the morphological differences. Group I differs from group II by the length of the midventral complex (65.1% vs. 52.5% of the cell length), the number of adoral membranelles (25–28 vs. 16–24), and the number of dorsal bristles in kinety 1 (16 bristles vs. nine bristles). Group I differs from the Antarctica population by the absence/presence of the collecting canals of the contractile vacuole and the number of macronuclear nodules (6–12 vs. 13–19). Group II differs from the Antarctica population by the number of macronuclear nodules (five to nine vs. 13–19); the arrangement of cortical granules (forming longitudinal rows vs. irregularly distributed); the length of the midventral complex (64.7% vs. 53.8% of cell length). In the phylogenetic analyses, A. sigmoidea was not nested with any species, and the gene tree indicated polyphyly of the genus Anteholosticha.